ANALYSIS OF STUDENTS' NUMERACY LITERACY SKILLS ON THE TOPIC OF SURFACE AREA AND VOLUME OF PRISMS - Luqman, Naufal; Zahra, Indry; Fadilah, Julva Rizky (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
This study aims to analyze students' numeracy literacy skills in solving problems related to the surface area and volume of prisms. Numeracy literacy is one of the essential competencies that students need to master in order to support problem-solving in daily life. The research method used is qualitative descriptive. The subjects of this study were 32 eighth-grade students from a junior high school in the city of Tasikmalaya. The research instrument was a mathematical numeracy literacy test consisting of essay and multiple-choice questions that had been validated by experts. The results of the study indicate that students' numeracy literacy skills, in general, are in the medium category, but there is a significant difference between students with high and low mathematical conceptual understanding. Students with a good understanding of mathematical concepts tend to have higher numeracy literacy skills, especially in solving problems related to calculating the volume of prisms. However, in questions requiring spatial reasoning and interpretation to calculate surface area, many students faced difficulties, particularly those with lower numeracy literacy skills. The discussion of these findings highlights the importance of strengthening basic mathematical concept understanding to improve students' numeracy literacy. The use of more interactive and contextual learning models can help students connect mathematical concepts to real-life situations. The implications of this research emphasize the need to improve the quality of mathematics teaching, focusing on the simultaneous development of numeracy literacy. Mathematics teachers are expected to design learning strategies that integrate concept strengthening with numeracy literacy practice in various everyday life contexts.Copyright © 2021Universit All rights reserved.